(untitled) (Razão e Fé, 2023)
The article intends to present, in a synthetic way, some of the trends of theology in Latin America. It chooses a path that combines history and some of the covered topics. It is not intended to be exhaustive, especial ly with regard to the current scenario. From a historical point of view, Liberation Theology and the option for the poor occupy a prominent place. This also determines the remaining topics covered, namely the matter of the place of women in theology, the relationship with Earth in the context of an ecological theology, and the relationship with both the cultural and religious origins of the Latin American population. By way of conclusion, the path followed by the decolonial perspective is pointed out, a path which seeks to explore the theological effect of the socalled epistemologies of the South.